Liposomal ferric pyrophosphate and ascorbic acid supplementation in pregnant women with iron deficiency anaemia: haematochemical, obstetric, neonatal and psychological outcomes in a prospective observational study. (17th February 2022) - Vitale, Salvatore Giovanni; Fiore, Maria; La Rosa, Valentina Lucia; Rapisarda, Agnese Maria Chiara; Mazza, Gabriele; Paratore, Marco; Commodari, Elena; Caruso, Salvatore
Abstract: This study aimed to determine the effects of liposomal iron pyrophosphate/ascorbic acid on clinical and psychological outcomes in pregnant women. Women at the 11th–13th weeks of gestation with iron deficiency anaemia assuming Sideremil™ from April 2018 to May 2019 were recruited. Haematochemical, obstetric, neonatal and psychological outcomes were investigated at the enrolment, 21–23 weeks of gestation, 30–32 weeks of gestation and after 6 weeks from childbirth. Results showed significant positive effects on haemoglobin, ferritin, sideremia and transferrin levels, compared to baseline data. A significant improvement of anxiety and depression levels was also observed. Regarding the quality of life, all the domains significantly improved, especially the Physical Role domain. Our results indicate that Sideremil ™ may be a valid treatment for iron deficiency anaemia in pregnant women, since it significantly improves haematological and mental health outcomes. However, further studies are needed to confirm these results.